2006
DOI: 10.1111/j.1574-6968.2005.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study ofvanAgene transfer fromEnterococcus faeciumtoEnterococcus faecalisand toEnterococcus faeciumin the intestine of mice

Abstract: Vancomycin-resistant enterococci represent a large reservoir in animals because of the use of avoparcin as a growth promoter in Europe. These strains of animal origin enter the food chain and can either colonize the human gut or transfer their resistance genes to the human microbiota. In this study, we compared the transfer of vancomycin resistance from resistant animal Enterococcus faecium to sensitive human Enterococcus faecalis and E. faecium. We analysed these transfers in dibiotic mice and human faecal fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 41 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…We focused on the analysis of these bacteria because they are Nasal ( (20). Similar findings were previously reported, however, for healthy volunteers and only for intestinal enterococci (10).…”
Section: Discussionsupporting
confidence: 56%
“…We focused on the analysis of these bacteria because they are Nasal ( (20). Similar findings were previously reported, however, for healthy volunteers and only for intestinal enterococci (10).…”
Section: Discussionsupporting
confidence: 56%
“…10 2 CFU/g of feces over 30 days and stabilized at this level (data not shown). This observation suggests an ecological disadvantage of transconjugant cells as previously described in transfer experiments between enterococci or other species [Andremont et al, 1985;Bourgeois-Nicolaos et al, 2006;Doucet-Populaire et al, 1991;Duval-Iflah et al, 1980, 1981Johnsen et al, 2002].…”
Section: In Vivo Transfermentioning
confidence: 56%
“…The potential contribution of probiotics needs further attention since preparations usually contain high titers of live bacteria and are generally consumed repeatedly. The human microbiota may, however, play a role as a potential barrier against emerging van R transconjugants [Bourgeois-Nicolaos et al, 2006;Lester et al, 2006;Mater et al, 2005]. Otherwise, probiotics should be used prudently in case of immunocompromised patients and also in antibiotherapy, since antibiotic pressure might favor the emergence of resistances.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of gene transfer from an exogenous strain to the indigenous flora can be related to the results of BourgeoisNicolaos et al (8), who found no transfer of the vanA gene from E. faecium to E. faecalis in a similar HFA model. Colonization resistance of the indigenous flora toward exogenous Salmonella has rapidly decreased the number of donor strain bacteria, whereas for transfer to occur, large numbers of both the donor and recipient strains must be present simultaneously (27).…”
Section: Discussionmentioning
confidence: 72%